Volunteering to take on power: Experimental evidence from matrilineal and patriarchal societies in India - Debosree Banerjee; Marcela Ibanez; Gerhard Riener; Meike Wollni (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
Gender equity in the creation and enforcement of social norms is important not only as a normative principle but it can also support long term economic growth. Yet in most societies, coercive power is in the hands of men. We investigate whether this form of segregation is due to inherent gender differences in the willingness to volunteer for take on positions of power. In order to study whether potential differences are innate or driven by social factors, we implement a public goods game with endogenous third-party punishment in matrilineal and patriarchal societies in India. Our findings indicate that segregation in coercive roles is due to conformity with pre-assigned gender roles in both cultures. We find that women in the matrilineal society are more willing to assume the role of norm enforcer than men while the opposite is true in the patriarchal society. Moreover, we find that changes in the institutional environment that are associated with a decrease in the exposure and accountability of the norm enforcer, result in increased participation of the segregated gender. Our results suggest that the organizational environment can be adjusted to increase representation of women in positions of power, and that it is critical to take the cultural context into account.
Keywords: C90; C92; C93; C92; D03; D70; D81; J16; 330; Gender; Norm enforcement; Segregation; Third party punisher; Public goods game